TANGGUNG JAWAB PELAKU USAHA ATAS PERBUATAN KARYAWAN YANG MENGAKIBATKAN KERUGIAN KONSUMEN (Analisis Putusan BPSK Kota Medan No.119/Arbitrase/BPSK-MDN/2014 - Hani Riadho Nasution; Hasim Purba; Dedi Harianto; Mahmul Siregar (USU LAW JOURNAL, 2018)
ABSTRACT   Responsibility is related to violation against a regulation and an obligation which has to be carried out based on an agreement and a legal provision. A business person can specify certain requirements without consumers’ consent. In consequence, consumers do not have any authority or right to realize the agreement in legal correlation. The research used descriptive analytical method with juridical normative approach. The data were gathered by conducting library research and collecting references dealing with the research object which includes secondary data obtained and gathered from the library research. The gathered data were analyzed qualitatively. The responsibility of a business person for his employee’s error in the case in BPSK of Medan is not fully his responsibility because consumers are protected by Law No 8/1999 on Consumer Protection. In the case of an automobile, Honda CRV, sold and used without any defect, the business person is not responsible anymore. The Ruling of BPSK Medan which accepts the claim from consumers is considered unjust by the business person because the content of the legal consideration does not analyze the error of the employee who has committed criminal act in forgery and the data of the consumer, but the objection of the business person by presenting evidence and witnesses is not considered.   Keywords: Responsibility, Employee’s Action, Consumer’s Loss